O trabalho encarcerado análogo à escravidão no movimento de acumulação de capital - Paula Cristina de Moura Fernandes (2023)
This thesis is part of the studies and researches of the Núcleo de Estudos Críticos Trabalho e Marxologia (Nec-TraMa), whose collective efforts have been to understand the contradictions of the concrete reality that finds its ultimate foundation in the productive forces of capital. And from the reflections about the contradiction in the relation Capital-Labor and its particularities in the penal system for the development and advance in the capitalist sociability, through Marxian categories of the Criticism of Political Economy, we elaborate the thesis that the work with slave-like characteristics in the prison system is one of the unfoldings of the advance of the capital in its general movement of accumulation and expanded reproduction. And to present the understanding of the real and the apprehension of the prison object in the general movement of the capital, we divide it into two parts. In the unveiling of the social relations of production we discuss how crime, and the naturalization of punishment, freedom, laws, and morality are products of the social relations of production, produced in and for the capitalist sociability, therefore they are limited and act in a way to obstruct class consciousness. Following the characteristics of these social relations, we identify five social functions that the prison assumes in the Capital-Labor relation. In detail, we have: i) to imprison as a form of punishment; ii) to cheapen the value of labor power; iii) to produce value in the production process, through public-private partnerships in productive activities; iv) to alter the technical composition of Capital to reduce costs and increase revenues; putting capitalists ahead in the dispute for the average profit, in the intra-capitalist struggle, and pointing out how imprisoned labor can come to serve as a means to equalize the rate of profit; v) to serve as an imprisoned reserve army. We also point out that this is not a movement particular to the Brazilian prison system. The accumulation movement is general, and goes through other countries, which allows us to present the possibility of the advance of Capital in prison as a tendency of capital due to its expansionist characteristics. In order to understand the continuities and ruptures of the social relations that reference the whole process of transformation of the relations of production, which goes through its time and are capable of evidencing the essence of the object, not restricting itself to its phenomenological aspects of the slave system in the capitalist sociability, we develop in part III an analysis from the gap presented by the authors Ghizoni and Vieira (2021), in which we present the concept, the contradictions and the particularity of labor analogous to slavery in prison as one of the expansionist movements of Capital. With this, based on the categories developed by Marx, supported by dialectical historical materialism, we conclude this thesis that presents the understanding of the real and apprehension of the object prison in the movement of accumulation and reproduction of capital in the capitalist sociability.